(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
Neuroscience has provided significant contributions on the brain in the last twenty years. Studies in this field have disconfirmed certain statements made in relation to the field of learning. These statements, called neuromyths, have been questioned from the latest research on the neural functioning. An examination of a neuromyth connected to the so-called learning styles is essential, including the so called VAK (visual, auditory, kinesthetic) learning styles. Technology has enabled us to study the brain functions live. This has shown that the processing of information is not linear, as would indicate learning styles; this process affects various nerve centers without absolute predominance of some over others. Moreover, scientific researchers have coined a new concept, neurodiversity, (Harvey Blume 1998), which realizes that each one of us carries a single brain configuration. These investigations have caused a significant impact on learning, inviting us to build bridges between the two disciplines and to rearrange our related knowledge and learn how to establish an efficient and effective student / teacher interaction in education.